2023
DOI: 10.1080/21695717.2022.2122334
|View full text |Cite
|
Sign up to set email alerts
|

Have newborn hearing screening programs been affected by the COVID-19 pandemic?

Abstract: Introduction Due to the vital importance of early diagnosis and intervention of congenital hearing loss, the aim of this study was to compare the rate of newborn hearing screening before and after the COVID-19 pandemic quarantine. Materials and methods In this study, the data related to 6144 newborns during two 18-month time periods before and after the onset of the COVID-19 pandemic quarantine, was analyzed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the rate in the current study was lower than a study that was similarly conducted in Ahvaz in 2021 and reported a rate of 4.36. This discrepancy may be because this study was carried out during the COVID-19 pandemic and the COVID-19 pandemic has adversely affected the implementation of newborn hearing screening programs [24].…”
Section: Total Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the rate in the current study was lower than a study that was similarly conducted in Ahvaz in 2021 and reported a rate of 4.36. This discrepancy may be because this study was carried out during the COVID-19 pandemic and the COVID-19 pandemic has adversely affected the implementation of newborn hearing screening programs [24].…”
Section: Total Resultsmentioning
confidence: 97%
“…The findings indicated that the probability of passing results in newborns without NICU admission was two times greater than in those with NICU admission. Other studies also found that NICU hospitalization for more than 5 days could be a risk factor for hearing loss [24][25][26]. Hearing loss caused by staying in NICU could be due to mechanical ventilation for asphyxia and respiratory distress of newborns in the NICU that adversely damages the peripheral auditory system function [2,26].…”
Section: Total Resultsmentioning
confidence: 98%